2017
DOI: 10.1038/jhg.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Population-based biobank participants’ preferences for receiving genetic test results

Abstract: There are ongoing debates on issues relating to returning individual research results (IRRs) and incidental findings (IFs) generated by genetic research in population-based biobanks. To understand how to appropriately return genetic results from biobank studies, we surveyed preferences for returning IRRs and IFs among participants of the Tohoku Medical Megabank Project (TMM). We mailed a questionnaire to individuals enrolled in the TMM cohort study (Group 1; n=1031) and a group of Tohoku region residents (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…In this study, nearly 90% of our participants were over 60 years old. This is consistent with our previous preference research based on residents of the Iwate and Miyagi prefectures, in which almost 76% of subjects were over 60 [6]. This may be because younger people are busy with work and child rearing, and could not find the time to participate in our genetics workshop.…”
Section: Participant Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, nearly 90% of our participants were over 60 years old. This is consistent with our previous preference research based on residents of the Iwate and Miyagi prefectures, in which almost 76% of subjects were over 60 [6]. This may be because younger people are busy with work and child rearing, and could not find the time to participate in our genetics workshop.…”
Section: Participant Characteristicssupporting
confidence: 90%
“…The highest rate of genetic result preference was 98%, both before and after the workshop. This preference rate was higher than the rates in the Tohoku Medical Megabank project's participants (88%) and residents of the Tohoku area (82%) in a previous study [6]. More of our participants preferred to be informed of their genetic results regarding lifestyle diseases and pharmacogenetics than adult-onset non-clinically actionable diseases and all genetic information, both before and after the genetics workshop.…”
Section: Participant Characteristicscontrasting
confidence: 65%
See 1 more Smart Citation
“…We were unable to perform medical care within the research framework of the TMM study; however, we aim to translate the results of the TMM study for wider genomic medicine research. Thus, by receiving training on clinical genetics, ToMMo GMRCs could be in charge of returning genomic results to participants [21]. That is, in this way, we hope that ToMMo GMRCs could become specialists in community-based healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is quite odd in the landscape of studies on the same topic. In fact, regardless of the settings and type of participants surveyed [e.g., general population (15,16), general population vs. research participants (17), patients (18,19), biobank effective participants vs. potential participants (20,21)], a great majority of studies found that the disclosure of individual results is well accepted and can be even positively influential in the decision to donate. However, a few studies have already highlighted certain specific signals of the difficulties in disclosing individual health information.…”
Section: Discussionmentioning
confidence: 99%